ASSESSMENT OF ANAEROBIC THRESHOLD IN FOOTBALL PLAYERS ON DIFFERENT POSITIONS, USING THE CONCONI TEST - Milan Cvetković; Slobodan Andrašić; Boris Popović; Dejan Orlić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Requirements and needs of properly programmed training process, especially in the pre-season, look for a precise definition of the functional parameters of all the players. The level of anaerobic threshold, as well as research on the same, may be a good indicator of proper dosage of loading. The aim of the research is to determine the differences in running speed and heart rate at the level of anaerobic threshold in relation to the position of the player. Methods: Age of the respondents in this study included boys from 14 to 16 years of age (60 football players). The sample of respondents was divided according to playing position, as follows: center-backs (12 players), wing-backs (15 players), midfielders (14 players), forwarders (13 players) and goalkeepers (6 goalkeepers). An estimation of maximum heart rate and anaerobic threshold was performed using the Conconi test - (Conconi et al. 1996). Prior to testing players had ten minutes to warm up and after a few minutes of rest the testing began. Players started with jogging test (10 km/h) and after every 200 m running speed was increased by 0.5 km/h. Within certain sections the load is constant which is achieved by increasing speed after each 200 m, and then maintaining that speed until the end of the section. After processing the results within the particular software ("Polar Precision Performance SW") the values needed for this research were collected. Multivariate methods MANOVA and discriminant analysis will be applied in the paper. Regarding the univariate procedures, ANOVA t-test and Roy's test shall be applied. The descriptive parameters, mean value, standard deviation (SD), minimum and maximum of all values, the coefficient of variation (CV) of confidence intervals, skewness as the measures of asymmetry, kurtosis as the measure of flatness and the value of the Kolmogorov-Smirnov test, shall be presented. Results: By using the multivariate analysis of variance and based on the results, no statistically significant difference was observed. Discriminant analysis, which is a superior method compared to multivariate analysis of variance, because in addition to the quantitative values of the analyzed features it also observes their mutual relationship, revealed no significant difference also. Univariate analysis confirmed the assumption, which means no significant differences were found between the groups regarding the observed variables. However, the mean values for midfield players in all monitored parameters were the highest. Discussion: The results of this study indicate similar estimates of values of the anaerobic threshold between the groups divided according to their playing position. However, the mean values for midfield players in all monitored parameters were the highest: heart rate at the anaerobic threshold (186.36 beats/min), running speed at anaerobic threshold (14.07 km/h) and percentage value of anaerobic threshold in relation to the maximum heart rate (92.07 %), which separates them from other playing positions and points to the existence of certain differences. Comparing the results of this study with research performed by Dillerna et al. (2012) shows that similar results were obtained, and the best results are achieved by female midfield players. Also, by measuring heart rate during official games, Coelho et al. (2011), within the sample of 26 players from U-17 and 18 players from U-20 category, found that midfield players, presented in percentage, spent the most of the time in the zone 3 (p<0.05), and spent more time in zone 4 compared to the forward players and center-backs (p<0.05). The above studies indicate a significantly higher engagement of midfield players compared to other positions. References: Coelho BD, Mortimer AL, Condessa AL, Morandi FR, Oliveira MB, Marins JC, Soares DD, arcia SE (2011). Rev. Bras. Cineantropom Desempenho Hum., 13 (5), 341-7. Conconi F, Grazzi G, Casoni I, Borsseto C, Ballarin E, Mazzoni G, Gatracchini M, Manfredini F (1996). Int. Journ. ff Sport Medicine, 17, 7-12. Da Silva SG, Kaiss L, Campos W, Ladewig I (1999). Journal of Sports Sciences, 17, 823. Dillern T, Ingebrigtsen J, Shalfawi S (2012). Serbian Journal of Sports Sciences, 6 (2), 43-9. Helgerud J, Engen L, Wisloff U, Hoff J (2001). Medicine & Science in Sports & Exercises, 33(11), 1925-31.